Comparison on space charge and voltage distribution of high voltage insulator subjected to different contamination levels - N. A. Samuri; Nordiana Azlin binti Othman; M. A. M. Piah; N. A. M. Jamail; H. Rosli (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents the study of space charge distribution on high voltage (HV) insulators under different levels of contamination. Two types of HV insulators were used in this work particularly glass and porcelain insulators. A string of 4-unit glass and porcelain insulators with 33 kV of lines voltage was designed and simulated using QuickfieldTM software. Four levels of contamination layer with different thickness have been applied on the surface of insulators to observe the effect of space charge distribution. Simulation results show that different types of insulators used at transmission lines give different effects on charge and voltage distribution. It is also found that the amplitude of charge for a single porcelain insulator is much higher compared to a single glass insulator. Similarly for a string of 4-unit insulators, the voltage distribution along the creepage distance of porcelain insulators is much higher compared to glass insulators under all contamination levels.